2010
DOI: 10.1103/physrevd.82.056004
|View full text |Cite
|
Sign up to set email alerts
|

Higgs boson production from gluon fusion in warped extra dimensions

Abstract: We present an analysis of the loop-induced couplings of the Higgs boson to the massless gauge fields (gluons and photons) in the warped extra dimension models where all standard model fields propagate in the bulk. We show that in such models corrections to the hgg and h couplings are potentially very large. These corrections can lead to generically sizable deviations in the production and decay rates of the Higgs boson, even when the new physics states lie beyond the direct reach of the LHC. 1 One of the main … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
90
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(104 citation statements)
references
References 81 publications
13
90
1
Order By: Relevance
“…At about the same time, an independent analysis of the Higgs couplings to gluons and photons appeared [20], which reached the opposite conclusions. In a recent paper [23], it was shown that the discrepancy between the two sets of results can be traced back to a subtlety in the calculation of the loop-induced Higgs couplings to gluons and photons.…”
Section: Jhep01(2014)173mentioning
confidence: 86%
See 1 more Smart Citation
“…At about the same time, an independent analysis of the Higgs couplings to gluons and photons appeared [20], which reached the opposite conclusions. In a recent paper [23], it was shown that the discrepancy between the two sets of results can be traced back to a subtlety in the calculation of the loop-induced Higgs couplings to gluons and photons.…”
Section: Jhep01(2014)173mentioning
confidence: 86%
“…Precision measurements of the Higgs-boson couplings to SM particles, which are accessible via studies of both the Higgs production cross sections and its decay rates into various final states, present unique opportunities to test the SM description of electroweak symmetry breaking and search for indirect hints of new physics. In the context of warped extra dimensions, Higgs physics has been studied by several authors [14][15][16][17][18][19][20][21][22][23]. The effect on the gg → h amplitude caused by the heavy b ′ state, the SU(2) R partner of the top quark predicted in RS models with custodial symmetry, was investigated in [14].…”
Section: Jhep01(2014)173mentioning
confidence: 99%
“…The results should be in general consistent with the rough estimates of Eqs. (39) and (40). Some differences observed can nevertheless be explained, (see also [38]) so that one can still be confident in the generic size of the flavor violating couplings predicted in the flavor anarchy paradigm in RS type scenarios with four generations.…”
Section: Numerical Results For Higgs Fcnc Couplingsmentioning
confidence: 99%
“…As Higgs production can be modified within warped scenarios due to flavor violating effects in the Higgs sector [40], it may be possible to distinguish signals coming from a fourth generation model within the SM (SM4) with those coming from a fourth generation model associated with a warped extra-dimension (or a composite scenario), and, given the searches for the Higgs boson underway at the LHC, such an analysis is timely. The inclusion of the fourth generation will also affect low-energy precision observables, as well as limits on rare decays.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation